Effectiveness of Prescription-Based CNS Stimulants on Hospitalization in Patients With Schizophrenia: A Nation-Wide Register Study. (1st April 2017) - Rohde, Christopher; Polcwiartek, Christoffer; Asztalos, Marton; Nielsen, Jimmi
Abstract: Objective: Negative symptoms and cognitive deficits are main features of schizophrenia but with limited treatment options. Earlier studies have suggested that central nervous system (CNS) stimulants have a small effect on these domains, but with inconclusive results. As the first study to date, we aimed to investigate whether CNS stimulants improve naturalistic outcomes (psychiatric admissions and antipsychotic use) in patients with schizophrenia. Methods: By using extensive health registers all patients with schizophrenia and their use of CNS stimulants in Denmark were identified. Two models were used to investigate the effectiveness of CNS stimulants in patients with schizophrenia between 1995 and 2014; a mirror-image model with 605 individuals, using paired t tests and Wilcoxon signed rank tests, and a follow-up study with 789 individuals, using a conditional risk-set model. Results: CNS stimulants use was associated with a reduction in number of psychiatric admissions from 3.43 (95% CI = 2.86 to 4.01) to 2.62 (95% CI = 1.99 to 3.25) ( P = .009), with a more pronounced reduction for women (mean difference: −1.37, 95% CI = −2.34 to −0.40, P = .006). Psychiatric bed-days were reduced by 40 (95% CI = 24.5 to 55.6, P < .001) for individuals with at least 1 admission before CNS stimulant use. In addition, the total amount of antipsychotic use (Defined Daily Dose [DDD]) was reduced ( P = .001). The Hazard rate ratio in psychiatric admissions between women taking CNS stimulants compared to women not taking CNS stimulants was 0.77 (95% CI = 0.67 to 0.88). Conclusion: CNS stimulants may have clinical potentials for improving functional outcomes in patients with schizophrenia and randomized clinical studies evaluating this topic are warranted.